2013
DOI: 10.1111/1365-2745.12171
|View full text |Cite
|
Sign up to set email alerts
|

An allelopathic plant facilitates species richness in the Mediterranean garrigue

Abstract: Summary1. Positive plant-plant interactions are known to increase species richness in stressful and poor habitats that are often species poor, but the role of facilitative interactions in species-rich communities is less well understood. It has been proposed that allelopathic plants may create non-transitive species interactions, which increase species coexistence, and that such indirect facilitation may be important in species-rich communities. 2. We examined species richness in 12 different plant communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…This local dominance possibly arose via a combination of positive nurse effect and intraspecific facilitation among A. sterilis plants (Schöb, Armas & Pugnaire ). Thyme soil is richer in nitrogen and organic matter than no‐thyme soil (Ehlers & Thompson ) and harbours a more species‐rich plant community (Ehlers, Charpentier & Grøndahl ). Several results suggest that competition is more severe on thyme soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This local dominance possibly arose via a combination of positive nurse effect and intraspecific facilitation among A. sterilis plants (Schöb, Armas & Pugnaire ). Thyme soil is richer in nitrogen and organic matter than no‐thyme soil (Ehlers & Thompson ) and harbours a more species‐rich plant community (Ehlers, Charpentier & Grøndahl ). Several results suggest that competition is more severe on thyme soil.…”
Section: Discussionmentioning
confidence: 99%
“…; Pakeman et al . ; Cavieres & Badano ; Ehlers, Charpentier & Grøndahl ). The engineer species may indirectly promote coexistence of each competitor by locally modifying the environment and generating a mosaic of microhabitats.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we expected that in drylands, where competition for space is not a dominant process, the allelopathic species would have a negative effect on diversity, in contrast to results found in mesic Mediterranean areas (Ehlers et al. ). Also, we hypothesized that if allelopathic compounds have determinant effects on germination and survival of other species present in community, only species adapted to allelochemicals will be able to coexist with the allelopathic species.…”
Section: Introductionmentioning
confidence: 86%
“…Ehlers et al. () found that the allelopathic Mediterranean species, Thymus vulgaris L., acts as diversity accumulator because it suppresses a superior competitor. In other words, allelopathy had positive net effects on diversity because of indirect facilitation (Brooker et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, I conclude that direct facilitation of CAM plants by trees occurs simultaneously with the indirect effect in situations of a low-to-moderate root overlap between trees and CAM plants. (Knipe and Herbel, 1966;Callaway, 2007;Ehlers et al, 2014). In contrast, other studies indicate that the indirect positive effect can be outweighed by the direct negative effect (Pagès et al, 2003 andPagès andMichalet, 2003), thus precluding the occurrence of indirect facilitation (Levin, 1999;Brooker et al, 2008).…”
Section: Parameterization Of the Modelmentioning
confidence: 98%